Analysis of Gibran Teguh's Online Blusukan Campaign Strategy at The 2020 Solo Elections - M Fitrah Naufal (Universitas Medan Area, 2022)
This paper aims to analyze the online blusukan campaign strategy used by the Gibran-Teguh in the 2020 Solo Regional Election. This is considered important to analyze because the situation in Indonesia, which is being hit by the COVID-19 pandemic, has changed the pattern of people's lives on all fronts, including politics. The candidates for regional heads and mayors are looking for new ways to campaign so that they do not violate the health protocols set by the government. In the Solo Election, one of the candidates, namely Gibran – Teguh, used an online blusukan campaign strategy. The author used the theory of mass society and network society from Jan Van Dijk to find out how this online blusukan strategy was applied to the Solo Election. This paper is conceptual research that uses a descriptive qualitative approach and literature study research methods. This study concludes that the online blusukan campaign strategy is by the types and conditions of the citizen of Solo.